Design Consideration Of A High Frequency Power Transformer - Razak, A.R.; Taib, S. (2003)
The approach of hlgh frequcncy application seems to be very trendy in powcr transformer design. Especially when it is greatly efficient ln reducing size, losses,cost etc. However, there is not much dlscussion that were made on how to deslgn tbe hlgh frequency power transformcr using a proper approach, cost efficient and reliable to be implemented,So in this paper, some of those importrnt parameters are brlefly consldered, The dlscusslon is made throughout their geometriess, core losses ,winding losses and thermal model consideration accordinly.